Labor Market Policies and IMF Advice in Advanced Economies during the Great Recession - Blanchard, Olivier (Staff Discussion Notes; Staff Discussion Notes ;, 2013)
This paper does two things. First, it articulates what are the main implications of theoretical and empirical research for design of labor market policies and labor market institutions. Second, in this light, the paper analyzes the IMF's labor market recommendations since the beginning of the crisis, both in general, and more specifically in program countries.